THE EFFECTIVENESS OF ROLE PLAY IN TEACHING SPEAKING AT THE EIGHT GRADE STUDENTS OF MTs NURUL FALAH KOTA CIMAHI - Hernayah Hernayah; Rifqi Fadlurrahman Syaubari; Acep Haryudin (PROJECT (Professional Journal of English Education), 2019)
Speaking is a part of language and one of important skills that should be learned by the students. Role Play is offered to overcome the problems in speaking. In fact, The Students face difficulties in speaking such as difficulty to arrange the sentences, fear or making mistakes, and lack of motivation The aim of this research was carried out to find the effectiveness of using Role Play in teaching speaking for second grade of junior high school at MTs Nurul Falah Kota Cimahi whether there is significance different in speaking achievement of the students who are taught without using a role play. The use of Role Play does not increase the students’ speaking skills. Alternative Hypothesis says that the use of Role Play increases the students’ Speaking skill. This research use Quantitative Method by SPSS for collecting the data The subject of the study were 33 students and the sample of population collected from second grade in junior high school. From the result of the analysis the students’ score of speaking is improve. It’s as a result of role play helps the back students by providing a chance, wherever students with problem in oral communication ar ligatedKeywords:  Speaking, Role Play, Motivation